The development of PQ4R-based LKPD to improve the fourth grade students’ thematic learning outcome - Anadya Tri Sabrini; Dwi Yulianti; Dina Maulina (International Journal of Educational Studies in Social Sciences (IJESSS), 2021)
This research aims to analyze the need of LKPD development in accordance with the learning model used. This research was a descriptive quantitative research. The research subjects were teachers and students of grade IV at State Elementary School (SDN) 2 Kampung Baru. The data were collected using interviews, observation, and questionnaire, which were analyzed through a descriptive analysis. The results show that the competence standard, basic competence, and competence achievement indicators were in line with the Curriculum 2013. The students’ learning outcomes were categorized into low category. The PQ4R is one of models that can be applied for improving students’ learning outcomes. The teachers need a suitable LKPD for the learning model, suitable with students’ characteristics. This research can be further developed referring to the PQ4R learning model for improving learning achievement.